2022
DOI: 10.1055/a-1894-7320
|View full text |Cite
|
Sign up to set email alerts
|

Supermicrosurgical Experience pertaining to Replantation of Tamai Zone 1 Fingertip Amputations

Abstract: With the advent of supermicrosurgery, the replantation of very distal finger amputations has become possible. The choice between replantation or flap surgeries in the treatment of Tamai Zone I finger amputations continues to be a matter of debate. This study aims to evaluate replantation results in Tamai Zone 1 finger amputations. The demographic characteristics and clinical results of 39 patients undergoing rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Pamuk 32 retrospectively analyzed the selection of replantation surgery or flap surgery in the Tamai Zone I fingertip amputation. He demonstrated that with the emergence of super microsurgery, these patients should undergo replantation surgery first.…”
Section: Discussionmentioning
confidence: 99%
“…Pamuk 32 retrospectively analyzed the selection of replantation surgery or flap surgery in the Tamai Zone I fingertip amputation. He demonstrated that with the emergence of super microsurgery, these patients should undergo replantation surgery first.…”
Section: Discussionmentioning
confidence: 99%